Linear Growth in Pediatric Kidney Transplant Population - Lopez-Gonzalez, Mercedes; Munoz, Marina; Perez-Beltran, Victor; Cruz, Alejandro; Gander, Romy; Ariceta, Gema (Frontiers in Pediatrics, 2020)
Introduction Growth retardation is one of the main complications of chronic kidney disease (CKD) in children and induces a negative impact on quality of life. Material and Methods Retrospective analysis of all consecutive patients younger than 18 years old who received a first KT in our center between 2008-2018. Results 95 first KT recipients, median age at KT of 7.83 years. At the time of KT, 65.52% of males and 54.05% females showed normal height. After transplantation, linear growth improved from -1.53 at transplant to -1.37 SDS height at the last visit. We detected a different linear growth pattern according to patient age at KT. Children younger than 3 years old exhibited the most significant growth retardation at baseline and the greatest linear growth over time (-2.29 vs -1.82 SDS height), whereas catch-up was not observed in older patients. Multivariate analysis showed that use of corticosteroids was negatively related to SDS height at one year after transplantation and final SDS height only was positively associated with SDS height at KT. 44.2% and 22.1% patients received rhGH treatment before and after KT. 71.88% patients reached adulthood with normal final height. Conclusions In our study pediatric KT recipients exhibited a normal height in more than half of cases at KT, and in more than two thirds at the final adult height. Only children younger than 6 years old presented a relevant growth catch up after KT. Treatment with rhGH was used before and after KT with significant improvement in height.